Benzothiazolyl COFs reinforced polymer electrolyte membrane, preparation method thereof and application of benzothiazolyl COFs reinforced polymer electrolyte membrane in all-solid-state lithium battery

By using benzothiazolyl COFs-enhanced polymer electrolyte membranes in solid-state lithium batteries, the problems of poor high-voltage stability, low ionic conductivity and high interface impedance of solid-state electrolytes are solved, and higher ionic conductivity and thermochemical stability are achieved, improving the overall performance of lithium batteries.

CN119890431APending Publication Date: 2025-04-25ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510074109.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The problems of poor high voltage stability, low ion conductivity and high interface impedance of solid electrolytes in solid-state lithium batteries affect the actual use of lithium-ion batteries.

Method used

A polymer electrolyte membrane with benzothiazolyl COFs as filler was designed, and the film was prepared by hot pressing, which improved the membrane's magnification and charge-discharge performance, and was used in all-solid-state lithium batteries.

Benefits of technology

Without losing the mechanical strength of the film itself, the ionic conductivity and thermal chemical stability of the lithium battery are improved, and the shortcomings and shortcomings of all-solid lithium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The invention discloses a benzothiazolyl COFs (Covalent Organic Frameworks) reinforced polymer electrolyte membrane, a preparation method thereof and application of the benzothiazolyl COFs reinforced polymer electrolyte membrane in an all-solid-state lithium battery. The polymer electrolyte membrane is prepared from polycaprolactone, lithium difluoro (oxalato) borate and benzothiazolyl COFs as raw materials. According to the invention, benzothiazolyl COFs is used as a filler to be used as a membrane material for manufacturing the polymer solid electrolyte, the performance of the membrane is improved under the condition of not losing the mechanical strength of the membrane, and when the membrane is applied to an all-solid-state lithium battery, the all-solid-state lithium battery shows excellent rate capability and potential window, and the performance of the all-solid-state lithium battery is improved. The invention provides a new way for effectively improving the performance of the all-solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer solid electrolytes, and specifically relates to a polymer electrolyte membrane designed and prepared using benzothiazolyl COFs as fillers, and application of the polymer electrolyte membrane in all-solid-state lithium batteries. Background Art

[0002] With the continuous consumption of energy and fossil fuels by humans, the energy crisis caused by it has received great attention from people. For this reason, finding reasonable and effective renewable resources is a top priority. It is worth noting that among various high-efficiency energy storage devices, lithium-ion batteries with advantages such as high energy density and high safety have attracted widespread attention. Among them, solid-state lithium-ion batteries have ushered in major opportunities. In solid-state lithium batteries, solid polymer electrolytes are one of its core components. Its excellent film-forming ability, good cycle ability and wide range of applications make it the focus of people's research. However, in today's research on solid-state electrolytes, many challenges that need to be overcome have been found, such as poor high-voltage stability, low ionic conductivity and high interface impedance. These problems have seriously affected the actual use of solid-state lithium-ion batteries. For this reason, it is necessary to find an excellent material to solve the current problems one by one.

[0003] In recent years, covalent organic frameworks (COFs) have been widely studied by scholars due to their excellent performance. Specifically, the combination of active functional groups and porous structures of COFs is beneficial to ion storage in rechargeable batteries. The neat nanopores with controllable size can promote special ion transport by forming selective diffusion channels, so that they can be used as ion sieves, separators and solid electrolytes in rechargeable batteries. The covalent bonds of COFs ensure their high thermal / mechanical stability, and the presence of amorphous lithium-conducting molecular chains on the COFs skeleton significantly improves the ionic conductivity. These properties can effectively improve the problems of solid electrolytes. However, COFs also have problems that need to be solved. For example, the mean free path is relatively low and the carrier separation efficiency is low. To this end, three benzothiazole COFs were designed, which can not only solve the problems of COFs themselves, but also add them to solid electrolytes to improve the side effects of solid-state lithium batteries. Summary of the invention

[0004] In view of the shortcomings and deficiencies of existing key materials and technologies in the field of solid-state batteries, the present invention provides a benzothiazolyl-based COFs enhanced polymer electrolyte membrane and a preparation method thereof and application in all-solid-state lithium batteries.

[0005] The polymer solid electrolyte membrane can be prepared by hot pressing film forming, and has the advantages of simple operation, simple synthesis, strong contrast, etc. In addition, the polymer solid electrolyte membrane can improve the rate and charge-discharge performance of the membrane without losing the mechanical strength of the membrane itself, and is used for an excellent potential window.

[0006] The technical solution of the present invention is as follows:

[0007] A benzothiazolyl COFs-enhanced polymer electrolyte membrane is prepared from polycaprolactone (PCL), lithium difluorooxalatoborate, and benzothiazolyl COFs as raw materials;

[0008] Based on the total mass of the membrane, the mass of lithium difluorooxalatoborate accounts for 20-30%, and the mass of benzothiazolyl COFs accounts for 0.1-2%;

[0009] The structural formula of benzothiazolyl COFs is shown as NS-COF-1, NS-COF-2 or NS-COF-3:

[0010]

[0011]

[0012]

[0013] The method for preparing the benzothiazolyl COFs enhanced polymer electrolyte membrane of the present invention comprises the following steps:

[0014] (1) taking a portion of polycaprolactone and dispersing it together with benzothiazolyl COFs in solvent a to obtain dispersion a; taking the remaining amount of polycaprolactone and dissolving it together with lithium difluorooxalatoborate in solvent b to obtain solution b; in a glove box, under stirring conditions, dropwise adding dispersion a into solution b, and fully stirring to form a mixed system;

[0015] Solvent a is selected from one or more of acetonitrile, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, chloroform, dichloromethane, and acetone;

[0016] Solvent b is selected from one or more of acetonitrile, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol, and isopropanol;

[0017] "Solvent a" and "Solvent b" have no special meanings. They are marked as "a" and "b" only to distinguish the solvents used in different operation steps;

[0018] The stirring rate is preferably 100 to 400 rpm, and the mixture is stirred for 12 hours to form a mixed system;

[0019] (2) pouring the mixed system obtained in step (1) onto release paper, placing it in a glove box to dry, and then placing it in a vacuum oven to dry, and finally hot pressing to form a film to obtain the benzothiazolyl-based COFs enhanced polymer electrolyte membrane;

[0020] Types of release paper include: polyethylene release paper, polytetrafluoroethylene release paper, silicone release paper;

[0021] Preferably, the mixture is placed in a glove box and dried for 24 hours; preferably, the temperature of the vacuum oven is 45 to 80° C. and the mixture is dried for 24 hours;

[0022] The preferred hot pressing temperature is 70°C and the hot pressing pressure is 10 MPa.

[0023] When the benzothiazolyl-based COFs-enhanced polymer electrolyte membrane of the present invention is applied to an all-solid-state lithium battery, the all-solid-state lithium battery exhibits excellent rate performance and potential window.

[0024] The beneficial effects of the present invention are:

[0025] The polymer solid electrolyte membrane provided by this discovery can improve the rate and charge-discharge performance of the membrane without losing the mechanical strength of the membrane itself, and has excellent electrochemical performance. The preparation process of the polymer membrane is simple and easy to operate, which can effectively reduce the occurrence of errors. The polymer solid electrolyte membrane synthesized by benzothiazole COFs not only has the thermochemical stability of the benzothiazole structure, but also has the advantages of COFs itself. Compared with traditional polymer electrolytes, COFs exhibit inherent free volume generated by periodic and rigid crystal structures, thus providing a fast Li + In addition, their intrinsic porosity accelerates Li+ transport by providing abundant ion conduction pathways or accommodating guest species. + Conductivity promotes ion conduction. Therefore, the polymer solid electrolyte membrane synthesized from benzothiazole COFs can effectively improve the ionic conductivity and thermochemical stability of lithium batteries at room temperature and improve the shortcomings and deficiencies of all-solid-state lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : Rate performance diagram of Comparative Example 1, Example 1, Example 2 and Example 3 of the polymer solid electrolyte prepared by the present invention at different rates.

[0027] Figure 2 : LSV diagrams of Comparative Example 1, Example 1, Example 2, and Example 3 of the polymer solid electrolyte prepared by the present invention.

[0028] Figure 3 : The charge and discharge curve diagram of Example 1 of the polymer solid electrolyte prepared by the present invention.

[0029] Figure 4 : The charge and discharge curve diagram of Example 2 of the polymer solid electrolyte prepared by the present invention.

[0030] Figure 5: The charge and discharge curve diagram of Example 3 of the polymer solid electrolyte prepared by the present invention.

[0031] Figure 6 : The charge and discharge curve diagram of Comparative Example 1 of the polymer solid electrolyte prepared by the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings, but the protection scope of the present invention is not limited thereto.

[0033] In the following examples, the PCL used is Aladdin, with a purity of ≈99% and a molecular weight of 30,000 to 190,000.

[0034] The preparation method of NS-COF-1 is as follows:

[0035] 2,5-Diamino-1,4-dithiophenol dihydrochloride (1.47 g, 6.0 mmol) was suspended and dispersed in 12 mL of dimethylacetamide, and 12.5 mmol of pyridine was added dropwise. The dispersion was added to a mixed system of 18.0 mmol of triethyl orthoacetate and 0.3 mmol of scandium trifluoromethanesulfonate through a syringe, stirred at 50 ° C for 1.5 hours, then cooled to room temperature and diluted with water. The crude reaction product was obtained by filtration and recrystallized with a mixed solvent of dichloromethane and n-hexane to obtain a white needle-shaped monomer 2,6-dimethylbenzene [1,2-d: 4,5-d'] bis (thiazole) (DBBT).

[0036] The thick-walled pressure tube was pre-filled with argon for 5 minutes to remove air, 0.3mmol DBBT, 0.2mmol 1,3,5-tris(4-formylphenyl)triazine, 7mL dimethylformamide, 3mL o-dichlorobenzene, and 2mL trifluoromethanesulfonic acid were added to the pressure tube, and ultrasonication was performed for ten minutes to fully disperse the product. The reaction tube was heated to 180℃ in a closed state for three days. After the reaction, the mixture was cooled to room temperature and 0.1mol L -1 The precipitated product was collected and washed with methanol, tetrahydrofuran and dichloromethane (50 mL of each solvent each time, repeated three times). The washed product was dried under vacuum at 60°C for 12 hours to obtain yellow NS-COF-1 powder.

[0037] The preparation method of NS-COF-2 is as follows:

[0038] Different from NS-COF-1, NS-COF-2 uses an equal molar equivalent of 1,3,5-tri(4-formylphenyl)benzene instead of 1,3,5-tri(4-formylphenyl)triazine during the synthesis process. The remaining processes and process parameters are the same as those of NS-COF-1 and will not be repeated here.

[0039] The preparation method of NS-COF-3 is as follows:

[0040] Different from NS-COF1, NS-COF-3 uses an equimolar equivalent of triformylphenylamine instead of 1,3,5-tri(4-formylphenyl)triazine during the synthesis process. The remaining processes and process parameters are the same as those of NS-COF-1 and will not be repeated here.

[0041] Example 1

[0042] Weigh 9.4 mg (1%) of NS-COF-1 and mix it with 0.1725 g PCL and 3.75 g acetonitrile to form a dispersion a, 0.5175 g PCL, 0.25 g lithium difluorooxalate borate and 11.75 g acetonitrile to form a solution b. Under stirring, the dispersion a is slowly dripped into the solution b to form a benzothiazole COF polymer solid electrolyte solution, and the oxygen and water content are both less than 0.01 ppm. Stir for 12 hours in a low-water oxygen glove box. Pour the electrolyte solution onto release paper and place it in the same low-water oxygen glove box for 24 hours. Then transfer the dried film that has been left to stand to 80°C in a vacuum oven for 24 hours to obtain a dry film that can be hot-pressed. Finally, the dry film is hot-pressed at 70°C and 10 MPa to form a film, and cut into a 16.5 mm diameter circular film in the instrument. The polymer solid electrolyte membrane with a thickness of 90 microns is used to test its performance in lithium batteries.

[0043] Example 2

[0044] Weigh 9.4 mg (1%) of NS-COF-2 and mix it with 0.1725 g PCL and 3.75 g acetonitrile to form a dispersion a, 0.5175 g PCL, 0.25 g lithium difluorooxalate borate and 11.75 g acetonitrile to form a solution b. Under stirring, the dispersion a is slowly dripped into the solution b to form a benzothiazole COF polymer solid electrolyte solution, and the oxygen and water content are both less than 0.01 ppm. Stir for 12 hours in a low-water oxygen glove box. Pour the electrolyte solution onto release paper and place it in the same low-water oxygen glove box for 24 hours. Then transfer the dried film that has been left to stand to 80°C in an oven for 24 hours to obtain a dry film that can be hot-pressed. Finally, the dry film is hot-pressed at 70°C and 10 MPa, and cut into a 16.5 mm diameter circular film in the instrument. The polymer solid electrolyte membrane with a thickness of 95 microns is used to test its performance in lithium batteries.

[0045] Example 3

[0046] Weigh 9.4 mg (1%) of NS-COF-3 and mix it with 0.1725 g PCL and 3.75 g acetonitrile to form a dispersion a, 0.5175 g PCL, 0.25 g lithium difluorooxalate borate and 11.75 g acetonitrile to form a solution b. Under stirring, the dispersion a is slowly dripped into the solution b to form a benzothiazole COF polymer solid electrolyte solution, and the oxygen and water content are both less than 0.01 ppm. Stir for 12 hours in a low-water oxygen glove box. Pour the electrolyte solution onto release paper and place it in the same low-water oxygen glove box for 24 hours. Then transfer the dried film that has been left to stand to 80°C in an oven for 24 hours to obtain a dry film that can be hot-pressed. Finally, the dry film is hot-pressed at 70°C and 10 MPa, and cut into a 16.5 mm diameter circular film in the instrument. The polymer solid electrolyte membrane with a thickness of 85 microns is used to test its performance in lithium batteries.

[0047] Example 4

[0048] Different from Example 1, while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-1 is changed to 0.94 mg (0.1%), and the rest is the same as Example 1. The measured circular membrane diameter is 16.5 mm and the thickness is 91 microns, which will not be repeated here.

[0049] Example 5

[0050] The difference from Example 2 is that while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-2 is changed to 0.94 mg (0.1%), and the rest is the same as Example 2. The measured circular membrane diameter is 16.5 mm and the thickness is 86 microns, which will not be repeated here.

[0051] Example 6

[0052] The difference from Example 3 is that while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-3 is changed to 0.94 mg (0.1%). The rest is the same as Example 3. The measured circular membrane diameter is 16.5 mm and the thickness is 93 microns, which will not be repeated here.

[0053] Example 7

[0054] Different from Example 1, while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-1 is changed to 4.7 mg (0.5%), and the rest is the same as Example 1. The measured circular membrane diameter is 16.5 mm and the thickness is 82 microns, which will not be repeated here.

[0055] Example 8

[0056] The difference from Example 2 is that while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-2 is changed to 4.7 mg (0.5%), and the rest is the same as Example 2. The measured circular membrane diameter is 16.5 mm and the thickness is 89 microns, which will not be repeated here.

[0057] Example 9

[0058] The difference from Example 3 is that while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-3 is changed to 4.7 mg (0.5%). The rest is the same as Example 3. The measured circular membrane diameter is 16.5 mm and the thickness is 94 microns, which will not be repeated here.

[0059] Example 10

[0060] Different from Example 1, while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-1 is changed to 18.8 mg (2%), and the rest is the same as Example 1. The measured circular membrane diameter is 16.5 mm and the thickness is 96 microns, which will not be repeated here.

[0061] Embodiment 11

[0062] The difference from Example 2 is that while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-2 is changed to 18.8 mg (2%). The rest is the same as Example 2. The measured circular membrane diameter is 16.5 mm and the thickness is 98 microns, which will not be repeated here.

[0063] Example 12

[0064] The difference from Example 3 is that while ensuring that other conditions remain unchanged during the synthesis of the polymer electrolyte membrane, the mass of NS-COF-3 is changed to 18.8 mg (2%). The rest is the same as Example 3. The measured circular membrane diameter is 16.5 mm and the thickness is 94 microns, which will not be repeated here.

[0065] Comparative Example 1

[0066] Weigh 15g of acetonitrile, 0.69g of PCL, and 0.25g of lithium difluorooxalate borate to form a polymer solid electrolyte solution, and stir it thoroughly in a glove box for 12 hours. Pour the electrolyte solution onto release paper and place it in a glove box for 24 hours. Then transfer the dried film that has been left to stand in an oven at 80°C for 24 hours to obtain a dry film that can be hot-pressed. Finally, the dry film is hot-pressed at 70°C and 10MPa, and cut in the instrument to obtain a circular film with a diameter of 16.5mm and a thickness of 92 microns. The polymer solid electrolyte membrane is used to test its performance in lithium batteries.

[0067] Test Example 1

[0068] The composite all-solid-state electrolyte membrane prepared above was assembled into a lithium iron phosphate / Li battery and its 0.1C charge and discharge cycle performance at room temperature was tested. The 0.1C charge and discharge test results of Examples 1-12 and Comparative Example 1 are shown in Table 1. The specific assembly process is as follows: the assembly of lithium batteries and other tests was carried out in a low-water oxygen glove box with an oxygen and water content of less than 0.01ppm, and the order of negative electrode shell → lithium sheet → COF electrolyte membrane → positive electrode sheet → gasket → spring → positive electrode shell was placed from bottom to top. After assembly, the positive electrode was assembled and pressed downward. The positive electrode sheet used is a mixture of 800 mg of lithium iron phosphate (LiFeO4), 100 mg of polyvinylidene fluoride (PVDF) and 100 mg of Ketjen black (KB) and ground. After grinding, 3 ml of N-methylpyrrolidone is added and stirred for 12 hours. After stirring, a glass plate is taken, the prepared aluminum foil is rinsed with anhydrous ethanol, fixed with tape, and coated with a 150 mm scraper. After coating, it is dried for 12 hours. Finally, the finished aluminum foil is cut into positive electrode sheets with a diameter of 12 mm and weighed and stored separately.

[0069] Table 1 Cyclic performance test of lithium iron phosphate / Li battery assembled with solid polymer electrolyte membrane prepared by benzothiazole COFs as filler

[0070]

[0071] It can be seen from Table 1 that the lithium iron phosphate solid-state lithium battery assembled using the benzothiazole COFs polymer electrolyte membrane synthesized by the present invention has better capacity, capacity retention rate and coulombic efficiency than that of Comparative Example 1, and the capacity is best and the coulombic efficiency is highest when the benzothiazole COFs addition amount is 1%.

[0072] In addition, from Figure 3-Figure 6It can be seen that at the same rate, the discharge specific capacity of Example 1 is the largest, and the discharge specific capacity of Comparative Example 1 is the smallest. In addition, there is a stable platform at 3.4V during the discharge process for both the Example and the Comparative Example, and there is an overpotential of 0.1V between it and the charging platform. As the charge and discharge rate increases, the discharge platform becomes lower and lower, the overpotential becomes larger and larger, and the discharge capacity becomes smaller and smaller. Figure 5 The overcharge phenomenon occurred in Example 3, indicating that there is an instability in the interface or decomposition of the solid polymer electrolyte. This is because there is a lack of appropriate interaction between NS-COF-3 and the main structure of the polymer electrolyte, and NS-COF-3 is a granular structure with a large specific surface area, resulting in a large interface resistance. During the charging process, the local high pressure at the interface causes the polymer to continue to decompose. Figure 1 It can be seen that the battery performance is best when the charge and discharge rate is 0.1C. Figure 2 It can be seen that between 2.5V and 4.75V, the current is maintained below 2μA, indicating that the benzothiazolyl-based composite polymer electrolyte is stable in this voltage range. Above 4.75V, the current increases rapidly, indicating that the composite polymer electrolyte is oxidized and decomposed.

[0073] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.

Claims

1. A benzothiazolyl-based COFs-enhanced polymer electrolyte membrane, characterized in that: It is made of polycaprolactone, lithium difluorooxalatoborate, and benzothiazolyl COFs as raw materials; The structural formula of benzothiazolyl COFs is shown as NS-COF-1, NS-COF-2 or NS-COF-3:

2. The benzothiazolyl-based COFs-enhanced polymer electrolyte membrane according to claim 1, characterized in that: Based on the total mass of the membrane, the mass of lithium difluorooxalatoborate accounts for 20-30%, and the mass of benzothiazolyl COFs accounts for 0.1-2%.

3. The method for preparing a benzothiazolyl COFs-enhanced polymer electrolyte membrane according to claim 1, characterized in that: The following steps are involved: (1) taking a part of the polycaprolactone and dispersing it together with benzothiazolyl COFs in solvent a to obtain dispersion a; taking the remaining amount of the polycaprolactone and dissolving it together with lithium difluorooxalatoborate in solvent b to obtain solution b; In a glove box, under stirring conditions, dispersion a is added dropwise to solution b, and stirred thoroughly to form a mixed system; (2) pouring the mixed system obtained in step (1) onto release paper, placing it in a glove box to dry, and then placing it in a vacuum oven to dry, and finally hot pressing it to form a film to obtain the benzothiazolyl-based COFs enhanced polymer electrolyte membrane.

4. The preparation method according to claim 3, characterized in that: In step (1), solvent a is selected from one or more of acetonitrile, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, chloroform, dichloromethane, and acetone.

5. The preparation method according to claim 3, characterized in that: In step (1), solvent b is selected from one or more of acetonitrile, dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol, and isopropanol.

6. The preparation method according to claim 3, characterized in that: In step (2), the hot pressing temperature is 70° C. and the hot pressing pressure is 10 MPa.

7. Application of the benzothiazolyl-based COFs-enhanced polymer electrolyte membrane in an all-solid-state lithium battery as claimed in claim 1.